(untitled) (Academicia Globe: Inderscience Research, 2022)
This article provides information about the role of words in our language and their use in many senses, as well as the types of use, the most common methods of semantic transfer in our speech. In addition, the works of our great linguists provide theoretical information and their views on the transfer of meaning, as well as on the means of increasing the attractiveness and effectiveness of speech in the formation of written speech.